On the suitability of ultrathin detectors for absorbed dose assessment in the presence of high‐density heterogeneities. Issue 8 (30th November 2016) - Bueno, M.; Carrasco, P.; Jornet, N.; Muñoz‐Montplet, C.; Duch, M. A.
Abstract : Purpose: The aim of this study was to evaluate the suitability of several detectors for the determination of absorbed dose in bone. Methods: Three types of ultrathin LiF‐based thermoluminescent dosimeters (TLDs)—two LiF:Mg, Cu, P‐based (MCP‐Ns and TLD‐2000F) and a 7 Li‐enriched LiF:Mg, Ti‐based (MTS‐7s)—as well as EBT2 Gafchromic films were used to measure percentage depth‐dose distributions (PDDs) in a water‐equivalent phantom with a bone‐equivalent heterogeneity for 6 and 18 MV and a set of field sizes ranging from 5 × 5 cm 2 to 20 × 20 cm 2 . MCP‐Ns, TLD‐2000F, MTS‐7s, and EBT2 have active layers of 50, 20, 50, and 30 μm, respectively. Monte Carlo (MC) dose calculations (PENELOPE code) were used as the reference and helped to understand the experimental results and to evaluate the potential perturbation of the fluence in bone caused by the presence of the detectors. The energy dependence and linearity of the TLDs' response was evaluated. Results: TLDs exhibited flat energy responses (within 2.5%) and linearity with dose (within 1.1%) within the range of interest for the selected beams. The results revealed that all considered detectors perturb the electron fluence with respect to the energy inside the bone‐equivalent material. MCP‐Ns and MTS‐7s underestimated the absorbed dose in bone by 4%–5%. EBT2 exhibited comparable accuracy to MTS‐7s and MCP‐Ns. TLD‐2000F was able to determine the dose within 2% accuracy. No dependence on the beam energy or field size was observed. The MC calculations showed that a 50 μ m thick detector can provide reliable dose estimations in bone regardless of whether it is made of LiF, water or EBT's active layer material. Conclusions: TLD‐2000F was found to be suitable for providing reliable absorbed dose measurements in the presence of bone for high‐energy x‐ray beams.